Temporal changes in the associations between diagnosed psychiatric disorders and dropping out of school early - Ringbom, Ida (SPRINGER, 2025)
Psychiatric problems are risk markers for poor educational attainment. The number of adolescents receiving treatment has increased. We investigated whether the association between psychiatric problems in early adolescence and dropping out of school had changed. We used the register-based 1987 and 1997 Finnish Birth Cohort studies, which include all live births in Finland. Hospital districts with incomplete records were excluded, leaving 25,421 participants born in 1987 and 32,025 born in 1997. The main outcome was not having applied for secondary education by the year the cohort members turned 18. Our main predictors were psychiatric and neurodevelopmental disorders diagnosed by specialized services during 1998-2003 and 2008-2013, when the cohort members were 10-16 years old. We found that 511 (2.0) of subjects born in 1987 and 499 (1.6%) born in 1997 dropped out of school. Having any diagnosis at 10-16 of age was associated with dropping out of school early in both cohorts: 3.9% in 1987 and 4.8% in 1997. The highest proportions were in the subgroup with autism spectrum disorders (ASD), 19.4% in 1987 and 16.2% in 1997. Dropping out early increased among adolescents diagnosed with any psychiatric or neurodevelopmental disorder, from 3.9 to 4.8%, with the clearest increase for learning disabilities, from 3.4 to 9.0%. Dropping out decreased for those with depression, from 4.5 to 2.1%. Adolescents with psychiatric and especially neurodevelopmental disorders, need effective interventions to prevent them dropping out of school early. Increased detection of psychopathology did not result in decreased dropout rates.